Benefits and Costs of Compliance of Sanitary Regulations in Livestock Markets: The Case of Rift Valley Fever in the Somali Region of Ethiopia - Nin-Pratt, Alejandro; Jabbar, Mohammad A.; Ehui, Simeon (2012)
An outbreak of Rift Valley Fever in East Africa in 1998-2000 led to an export ban by Saudi Arabia and other Gulf countries on livestock products from Ethiopia lasting several years. An evaluation of the costs of the ban on Ethiopia's main exporting region (Somali) and their distribution among different types of households, producers and traders is conducted using a CGE model. Investment strategies to regain access to the Gulf market and reduce the probability of future bans are also evaluated. Results show that GDP in the Somali region is reduced by 36 percent as a consequence of the ban. In addition, poor and better off producers experience total losses in value added of around 50 percent of their respective levels in a normal year. The evaluation of an animal health program to minimize the impact of future bans shows that it increases welfare and benefits poor livestock producers.